The reality of transitions - Cordova, S (Refugee Studies Centre, University of Oxford, 2016)
Attempts to address the drivers of forced displacement and to provide sustainable solutions for refugees, IDPs and returnees need a more nuanced understanding of the drivers of violence and of war-to-peace transitions.